Development of Listening and Speaking Textbook for General Communication Based on Laboratory Language Operating Software - Roni La'biran; Melki Garoga; Perdy Karuru; Eka Apriani (Journal of English Education and Teaching, 2023)
This study aims to produce the development of a listening and speaking textbook for general communication based on laboratory language operating software viewed from the validation result of expert materials, expert design, media expert and students’ need This study uses, ADDIE consists of analysis, design, development, implementation and evaluation. Data collection and analysis techniques used in this research and development are data generated through interviews, observation, documentation, through informant and questionaries involving respondents analyzed descriptive qualitative. Findings of the development of English language teaching materials audio – based visuals can improve students’ language skills at a very good level. This evidenced by knowing the result of preliminary pre-test students of English department at UKI Toraja before the development of the textbook of listening and speaking for general communication with score 75,04 is enough level. After teaching materials development based on language laboratory operation software, the value of language skill of English department at UKI Toraja increased with the score 88,28 was at very good level and the average percentage of the survey results on student satisfaction in using the book development shows 80.35%. Teaching listening and speaking for general and communication based on laboratory language operating software can provide convince in teaching and learning process, thus impacting the effectiveness of learning. Thus, audio-visual materials based on audio- visual can be considered for lecturers in delivery the subject metter to make it more interesting and fun.